Sisal wool skin disease in Merino sheep in the Argentine Patagonia region: Identification and molecular diagnosis of Corynebacterium bovis from skin lesions - Abdala, Alejandra Mariana; Farber, Marisa Diana; Robles, Carlos Alejandro (Wiley, 2022)
Background: Sisal wool condition is a skin disease affecting Merino sheep in the Argentine Patagonia region. Corynebacterium spp. isolates have previously been isolated from skin swabs from lesions, while specific identification of the bacteria involved has not been reported. Hypothesis/Objectives: The aim of this work was to characterize the bacterial agent isolated from sisal wool lesions and to develop a diagnostic method for field surveillance. Materials and Methods: Molecular identification of a collection of 72 isolates obtained previously was performed using PCR and 16S rRNA and rpoB sequencing. A field survey was carried out on two farms in the Río Negro province of Argentine Patagonia. Swab samples from sheep with and without skin lesions were collected and analysed by PCR and culture. Results: Isolates analysed were confirmed by sequencing as Corynebacterium bovis. Using a PCR test without culture step, all field samples from affected sheep were positive for C. bovis; samples from the healthy skin from the same animals or clinically healthy sheep all were negative. Conclusions and clinical relevance: Sisal wool skin disease was associated with C. bovis infection based on culture and PCR methods; the latter may be useful for helping to pursue a disease control strategy.